AUDIT ENERGI LISTRIK PT. NIAGA NUSA ABADI DENGAN MENGGUNAKAN METODE INTENSITAS KONSUMSI ENERGI (IKE) DAN PELUANG HEMAT ENERGI (PHE) - Gunawan, Wawan; Zakaria, Tatan; Ridlo, Muhammad Alfi (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2024)
PT. Niaga Nusa Abadi is a company engaged in sales, distribution and marketing. Established in 2012. It is known that PT. Niaga Nusa Abadi has never carried out an energy audit since the company was founded. After collecting data, it can be seen that the lighting and air conditioning in several rooms do not comply with SNI standards. Energy audit technique used to calculate the amount of energy consumption in a building. Energy Consumption Intensity (IKE) is the quotient between total energy consumption during a certain period (one year) and the building area. The IKE unit is kWh/m2 per year. Energy saving opportunities are the potential to reduce energy use in a particular system or process in an efficient manner without compromising comfort. PT. Niaga Nusa Abadi has an area of ​​713.42 m2, an office with an area of ​​139.5 m2 and a warehouse with an area of ​​574.24 m2. After carrying out calculations, it can be seen that the initial energy audit is 52.77 Kwh/m2 per year. Carrying out detailed energy audit calculations of 46.79 Kwh/m2 per year. Recalculating the energy audit after carrying out improvements to lighting and air conditioning, it was found to be 52.27 Kwh/m2 per year. After making improvements to the lighting system and air system (AC), it is ideal and meets SNI standards. IKE after making improvements amounting to 52.27 kWh/m2 per year. IKE after carrying out repairs experienced an increase of 10% but the suitability and comfort of building users can be fulfilled and can increase user productivity